Korelasi antara self-efficacy dengan tingkat kesiapsiagaan mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi dalam menghadapi bencana alam - Simangunsong, Natasya Glory Meicharisty; Wariki, Windy Mariane Virenia; Rombot, Dina Victoria (Jurnal Kedokteran Komunitas dan Tropik, 2023)
Background: Natural disasters have a major contribution to the crisis of public health. A person's self-efficacy against his abilities can affect preparedness in dealing with disasters. Medical students as prospective doctors must be prepared to be able to provide health services to the community and prepare for natural disasters.Aim: This study aims to determine the correlation between self-efficacy and the level of preparedness of students of the Medical Doctor Study Program, Faculty of Medicine, Sam Ratulangi University in dealing with natural disasters.Methods: The type of research used is quantitative with an observational analytical research approach with a cross-sectional research design. The sampling technique uses simple random sampling and the research instrument uses questionnaires on self-efficacy and preparedness.Result: The results showed that most of the self-efficacy and preparedness of students of the Medical Doctor Study Program, Faculty of Medicine, Sam Ratulangi University, Manado was in the medium self-efficacy category.Conclusion: There was a significant correlation with the weak positive direction between self-efficacy and the level of student preparedness.Keywords: self-efficacy, preparedness, natural disaster